Partição de recursos alimentares entre os morcegos (Mammalia, Chiroptera) da planície de inundação do alto rio Paraná (Mato Grosso do Sul, Brasil) e a influência de pequenos fragmentos na sua diversidade. - Zanon, Cibele Maria Vianna (2010)
The present study addresses food resources partitioning of four frugivorous bats species: Carollia perspicillata (Linnaeus, 1758), Artibeus lituratus (Olfers, 1818), Platyrrhinus lineatus (E. Geoffroy, 1810) and Sturnira lilium (E. Geoffroy, 1810), and the influence of small forest fragments on bats diversity that occur in these fragments, considering that behavior ecology postulates that less species and more individuals occupy the transition zones, and that more species with smaller number of individuals reach for the forest nucleus. During 15 months, 247 individuals of 13 species were captured in 45 periodic samplings in a 3,6 ha seasonal SEMIDECIDUAL forest, located in the upper course of the Paraná River floodplain. The aim of the study was to test if four species of frugivorous bats search for different food resources, avoiding direct competition. A total of 41 feces samples were analyzed. All the four species are sympatric and exploit the environment in different ways; they might compete, however they coexist due to the ingestion of different resources. Data confirm their importance in the dispersal of several plant groups, mainly of the genus Piper, Solanum and Ficus. To test the board effect, eight species, with 116 individuals, were captured in the boarder; eight, with 68 individuals, collected 25m away from the boarder, and ten, with 63 individuals, collected in the fragment nucleus. We assumed that the fragment is not large enough to maintain constant bats populations, due to its small size and lack of quality to support several species. Differently of the boarder, the forest nucleus presents less alterations in the woods structure, which provides protection to a larger number of species; however, in smaller fragments, there is a population decay due to the nucleus reduced size. To maintain bats diversity, forest fragments with a reasonable nucleus size are required, were a larger number of species may coexist.